2008
DOI: 10.1016/j.cognition.2007.12.004
|View full text |Cite
|
Sign up to set email alerts
|

What is embodiment? A psychometric approach

Abstract: What is it like to have a body? The present study takes a psychometric approach to this question. We collected structured introspective reports of the rubber hand illusion, to systematically investigate the structure of bodily self-consciousness. Participants observed a rubber hand that was stroked either synchronously or asynchronously with their own hand and then made proprioceptive judgments of the location of their own hand and used Likert scales to rate their agreement or disagreement with 27 statements r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
1,062
5
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 820 publications
(1,139 citation statements)
references
References 50 publications
68
1,062
5
4
Order By: Relevance
“…Significant effects of condition were observed for all items, except items (4) and (5), which concern the transfer of structural properties from the real to the rubber hand and vice versa. This pattern is similar to that obtained in other RHI studies (e.g., Botvinick & Cohen, 1998;Longo, Schüür, Kammers, Tsakiris, & Haggard, in press). *** INSERT FIGURE 4 ABOUT HERE *** We next investigated how these phenomenal experiences of the RHI relate to the VET effect.…”
Section: Subjective Reports Of Rubber Hand Illusionsupporting
confidence: 90%
“…Significant effects of condition were observed for all items, except items (4) and (5), which concern the transfer of structural properties from the real to the rubber hand and vice versa. This pattern is similar to that obtained in other RHI studies (e.g., Botvinick & Cohen, 1998;Longo, Schüür, Kammers, Tsakiris, & Haggard, in press). *** INSERT FIGURE 4 ABOUT HERE *** We next investigated how these phenomenal experiences of the RHI relate to the VET effect.…”
Section: Subjective Reports Of Rubber Hand Illusionsupporting
confidence: 90%
“…A second related worry concerns the scale of ownership used in questionnaires, which often goes from À3 (strongly disagree) to +3 (strongly agree). For instance, in a study with 131 subjects, ownership was rated only at +0.4 in synchronous condition and at À1.2 in asynchronous condition (Longo, Schüür, Kammers, Tsakiris, & Haggard, 2008). These results are difficult to interpret.…”
Section: Depersonalizationmentioning
confidence: 91%
“…But this view uses a narrow definition of the notion of embodiment, restricting it to spatial aspects. Third, ownership is conceived as a subcomponent of embodiment: the sense of embodiment consists in what it is like to have a body, and includes the sense of ownership among other experiences (Longo et al, 2008). I am more sympathetic with the latter conception, which uses a notion of embodiment wide enough to capture the peculiar relation to the body of all the various described cases, from allograft to tool.…”
Section: Depersonalizationmentioning
confidence: 99%
“…self-location (as measured by proprioceptive drift) and body ownership (as measured by subjective ratings). Accordingly, Longo et al (Longo, Schüür, Kammers, Tsakiris, & Haggard, 2008) performed a principal component analysis of an extensive set of questionnaire responses about the RHI in order to identify the main components of the process of embodying a rubber hand (see Tajadura-Jimenez, Longo, Coleman, & Tsakiris, 2012 for the same approach to the ''enfacement'' illusion). Longo et al (Longo et al, 2008) clearly found that ownership and location, although strongly linked, were independent components in their analyses, suggesting that they independently contribute to the RHI.…”
Section: Neural Bases Of Whole-body Ownership and Self-locationmentioning
confidence: 99%